A Note on the Convergence of the Schrödinger Operator along Curve (Analysis in Theory and Applications, 2022)
In this paper we set up a convergence property for the fractional Schödinger operator for $0
Keywords: Refinement of the Carleson problem; disconvergence set; fractional Schrödinger operator; Hausdorff dimension; Sobolev space.